Agglutinative language in bahasa Indonesia - Gilang Febrian; Ulfa Novitasari; Arif Hidayat (Mitra Palupi, 2022)
Background: Morphology, defined as the internal structure of words, has always played an important role in linguistic typology, and it is with the morphological classification of languages into fusional, agglutinative, and isolation This paper will take one language as an example or object that is Indonesian language, and analysis the morphological typology characteristics in the Indonesian language. Purpose: This research is to find out the all characteristic of the morphology typology and analysis Indonesian language based on the agglutinative language because Indonesian language has same type with agglutinative language. Design and methods: This paper using descriptive qualitative method. The author analysis all of morphology typology branch especially agglutinative. To support analysis, the author using theory from other journal to strength the result of analysis. Results: The result show the Indonesian language is included to agglutinative language based on the analysis.